High throughput deep sequencing reveals the important roles of microRNAs during sweetpotato storage at chilling temperature. Issue 1 (December 2017) - Xie, Zeyi; Wang, Aiming; Li, Hongmin; Yu, Jingjing; Jiang, Jiaojiao; Tang, Zhonghou; Ma, Daifu; Zhang, Baohong; Han, Yonghua; Li, Zongyun
Abstract Sweetpotato (Impomoea batatas L .) is a globally important economic food crop with a potential of becoming a bioenergy and pharmaceutical crop. Thus, studying the molecular mechanism of tuberous root development and storage is very important. However, not too much progress has been made in this field. In this study, we employed the next generation high-throughput deep sequencing technology to sequence all small RNAs and degradome of sweetpotato for systematically investigating sweetpotato response to chilling stress during storage. A total of 190 known microRNAs (miRNAs) and 191 novel miRNAs were identified, and 428 transcripts were targeted by 184 identified miRNAs. More importantly, we identified 26 miRNAs differentially expressed between chilling stress and control conditions. The expression of these miRNAs and their targets was also confirmed by qRT-PCR. Integrated analysis of small RNAs and degradome sequencing reveals that miRNA-mediated SA signaling, ABA-dependent, and ROS response pathways are involved in sweetpotato root response to chilling stress during storage.